KI effects on corrosion inhibition for 1018 steel in acid media using Medicago sativa - Rodríguez-Torres, A.; Valladares-Cisneros, M. G.; Saldaña Heredia, A.; González-Rodríguez, J. G. (Frontiers in Chemistry, 2022)
Medicago sativa (M. sativa) extract is a safe and ecofriendly corrosion inhibitor of 1018 steel in acid media. The inhibitor reached a maximum efficiency of 85% by using 500 ppm. In this work, we study the use of KI as add-on to increase the inhibition efficiency of M. sativa, as well as making the natural inhibitor competitive with commercial ones. It was evaluated the effect of halide ions through the variation of different concentrations of KI, and its synergy with the extract of M. sativa as a corrosion inhibitor of carbon steel in 0.5 M sulfuric acid and different temperatures. The results were obtained through electrochemical techniques such as electrochemical impedance spectroscopy (EIS), potentiodynamic polarization curves (PDP) and weight loss gravimetric technique. It was found that halide ions increase the inhibition efficiency of M. sativa from 85% to 95% when 5 mM concentration of KI was used. The efficiency of the inhibition increases proportionally with the immersion time, but reduces when temperature increase. The addition of iodide ions (I−) revealed that it exerts a synergistic effect on the inhibition of corrosion with the extract of M. sativa. However, when studying the metal surface through the scanning electron microscope, pitting corrosion was found.